Usulan Alat Pelindung Diri (APD) dibagian Produksi Pada PT.FLA Untuk Memenuhi Requirement OHSAS 18001:2007 - Faadhila Alwi; Wiyono Wiyono; Heriyono Lalu (eProceedings of Engineering, 2019)
Abstractâ”€â”€PT. FLA is one of the manufacturing companies that produce drug presses, the types of tools are various types of systems from the company is the preorde according to customer demand. Based on observations found some problems one of which is incomplete Self-Protective tools in the company especially on the production floor. Activities that use equipment and raw materials in the production process have a risk of workplace accidents. One effort that can be done to reduce workplace accidents is the presence of personal protective equipment (PPE) in the company. The purpose of this research is to reduce workplace accidents at every activity in the company. This research was conducted by identifying hazards first, data obtained from interviews with several speakers who understood the production floor. After identifying hazards, then assessing these hazards, this assessment aims to see what hazards need to be followed up, after further assessment. Which results are the determination of personal protective equipment in accordance with the company. The work follow-up was based on OHSAS 18001: 2007 and PPN. 50 of 2012 concerning K3. Keywords: Personal Protective Equipment, Risk Assessment, Work Accident, Proposal, OHSAS 18001: 2007